2012
DOI: 10.1007/s10741-012-9367-2
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: an affair of the heart

Abstract: Whether an element of routine housekeeping or in the setting of imminent disaster, it is a good idea to get one’s affairs in order. Autophagy, the process of recycling organelles and protein aggregates, is a basal homeostatic process and an evolutionarily conserved response to starvation and other forms of metabolic stress. Our understanding of the role of autophagy in the heart is changing rapidly as new information becomes available. This review examines the role of autophagy in the heart in the setting of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 58 publications
1
54
0
Order By: Relevance
“…1; * P<0.05 vs. the control group). These findings suggested an enhancement of autophagy in this A/R model and was consistent with a previous finding that autophagy was activated in the heart at baseline and further enhanced during I/R [2] . …”
Section: Activation Of Autophagy In A/rsupporting
confidence: 93%
See 1 more Smart Citation
“…1; * P<0.05 vs. the control group). These findings suggested an enhancement of autophagy in this A/R model and was consistent with a previous finding that autophagy was activated in the heart at baseline and further enhanced during I/R [2] . …”
Section: Activation Of Autophagy In A/rsupporting
confidence: 93%
“…Recently, a study showed that autophagy is easily detected under basal condition in heart, and it is further induced during I/R [2] . Autophagy is a dynamic process of intracellular bulk degradation in which cytosolic proteins and organelles are sequestered into double-membrane vesicles, called autophagosomes, to be fused with lysosomes for degradation [3] .…”
mentioning
confidence: 99%
“…Our studies suggest that stimulation of cellular autophagy may also provoke ␤ 2 AR trafficking through autophagosomes. Autophagic activity is augmented in failing hearts (58), but whether this pathway is beneficial or detrimental for cardiomyocyte survival remains controversial (59). Deciphering the relationship between induction of autophagy, trafficking of ␤ARs, and activity of USP20 in healthy versus diseased hearts constitutes an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in I/R injury is controversial [37,38] . In cardiac acute I/R injury, autophagy mediated by AMPactivated protein kinase during ischemia is beneficial, whereas beclin-1-mediated autophagy during reperfusion is detrimental [9] .…”
Section: Discussionmentioning
confidence: 99%